2013
DOI: 10.1371/journal.pone.0056129
|View full text |Cite
|
Sign up to set email alerts
|

Association between Reduction of Plasma Adiponectin Levels and Risk of Bacterial Infection after Gastric Cancer Surgery

Abstract: Background and PurposeInfections are important causes of postoperative morbidity after gastric surgery; currently, no factors have been identified that can predict postoperative infection. Adiponectin (ADN) mediates energy metabolism and functions as an immunomodulator. Perioperative ADN levels and perioperative immune functioning could be mutually related. Here we evaluated a potential biological marker to reliably predict the incidence of postoperative infections to prevent such comorbidities.MethodsWe analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Adiponectin improves insulin sensitization and anti-inflammation and the lower expressed protein increases the resistance of insulin in fat and diabetic persons 31. The levels of adiponectin are lower in T2DM patients than in healthy participants 32.…”
Section: Resultsmentioning
confidence: 99%
“…Adiponectin improves insulin sensitization and anti-inflammation and the lower expressed protein increases the resistance of insulin in fat and diabetic persons 31. The levels of adiponectin are lower in T2DM patients than in healthy participants 32.…”
Section: Resultsmentioning
confidence: 99%
“…These results are meeting with the study of (Uji et al, 2010) who found that the plasma adiponectin levels decreased at the early period of polymicrobial sepsis and early detection of low adiponectin may help in management of patients with sepsis as an assessment of the severity of septic process [48]. A recent study by Yamamoto and his colleagues found that adiponectin ratio could be the most useful predictor for postoperative infection in comparison with CRP [49].…”
Section: Discussionmentioning
confidence: 69%
“…18 Others have shown that elevated preoperative circulating adiponectin was significantly associated with the development of postoperative infection, although these authors did not disaggregate SSI and remote infections. 16 To date, however, links between local adipose tissue and wound complications have not yet been reported despite adipose standing as the dominant tissue volume in the surgical wound (and thus a potential contributor to wound events via paracrine signaling).…”
Section: Discussionmentioning
confidence: 99%